IMPROVEMENT OF RECONSTRUCTIVE SURGERY FOR FRACTURES OF THE MANDIBLE - Akhrorov Alisher Shavkatovich (Web of Journals Publishing, 2024)
This article explores recent advancements in reconstructive surgery for mandibular fractures. The focus is on the development of surgical techniques, materials, and technologies that have enhanced patient outcomes. A review of current literature and case studies is presented to analyze the methods and challenges in the field. Emphasis is placed on the application of three-dimensional (3D) imaging, biocompatible materials, and minimally invasive procedures in mandibular reconstruction.
Keywords: Mandibular fractures, reconstructive surgery, 3D imaging, biocompatible materials, minimally invasive techniques, osteosynthesis, bone grafts.